Impact of referral templates on the quality of referrals from primary to secondary care: a cluster randomised trial - Wåhlberg, Henrik; Valle, Per Christian; Malm, Siri; Broderstad, Ann Ragnhild (BMC Health Services Research, 2015)
Background: The referral letter is an important document facilitating the transfer of care from a general practitioner (GP) to secondary care. Hospital doctors have often criticised the quality and content of referral letters, and the effectiveness of improvement efforts remains uncertain. Methods: A cluster randomised trial was conducted using referral templates for patients in four diagnostic groups: dyspepsia, suspected colorectal cancer, chest pain and chronic obstructive pulmonary disease. The GP surgery was the unit of randomisation. Of the 14 surgeries served by the University Hospital of North Norway Harstad, seven were randomised to the intervention group. Intervention GPs used referral templates soliciting core clinical information when initiating a new referral in one of the four clinical areas. Intermittent surgery visits by study personnel were also carried out. A total of 500 patients were included, with 281 in the intervention and 219 in the control arm. Referral quality scoring was performed by three blinded raters. Data were analysed using multi-level regression modelling. All analyses were conducted on intention-to-treat basis. Results: In the final multilevel model, referrals in the intervention group scored 18 % higher (95 % CI (11 %, 25 %), p < 0.001) on the referral quality score than the control group. The model also showed that board certified GPs and GPs in larger surgeries produced referrals of significantly higher quality. Conclusion: In this study, the dissemination of referral templates coupled with intermittent surgery visits produced higher quality referrals. Trial registration: This trial has been registered at ClinicalTrials.gov. The trial registration number is NCT01470963.